The global bazaar economy - Biao Xiang (economic sociology. perspectives and conversations, 2022)
A global bazaar is a marketplace where small, independent enterprises buy and sell a wide range of goods globally and directly, without relying on a centralized mediator. Typical examples of global bazaars are the Yiwu Market (officially the "International Trade City") in southeast China and the Dubai markets (the Dubai Wholesale City and a group of specialized marketplaces such as the Deira Covered Shoes Market) in the UAE.
Keywords: 300